Is lower hip range of motion a risk factor for groin pain in athletes? A systematic review with clinical applications - Tak, I.; Engelaar, L.; Gouttebarge, V.; Barendrecht, M.; Van den Heuvel, S.; Kerkhoffs, G.; Langhout, R.; Stubbe, J.; Weir, A. (British Journal of Sports Medicine, 2017)
Background: Whether hip range of motion (ROM) is a risk factor for groin pain in athletes is not known. Objectives: To systematically review the relationship between hip ROM and groin pain in athletes in cross-sectional/case-control and prospective studies. Study design: Systematic review, prospectively registered (PROSPERO) according to PRISMA guidelines. Methods: Pubmed, Embase, CINAHL and SPORTDiscus were systematically searched up to December 2015. Two authors performed study selection, data extraction/analysis, quality assessment (Critical Appraisal Skills Programme) and strength of evidence synthesis. Results: We identified seven prospective and four case-control studies. The total quality score ranged from 29% to 92%. Heterogeneity in groin pain classification, injury definitions and physical assessment precluded data pooling. There was strong evidence that total rotation of both hips below 85° measured at the pre-season screening was a risk factor for groin pain development. Strong evidence suggested that internal rotation, abduction and extension were not associated with the risk or presence of groin pain. Conclusion: Total hip ROM is the factor most consistently related to groin pain in athletes. Screening for hip ROM is unlikely to correctly identify an athlete at risk of developing groin pain because of the small ROM differences found and poor ROM measurement properties.